Operative and Conservative Treatment of Uterine Sarcomas - Harter, P.; El-Khalfaoui, K.; Heitz, F.; du Bois, A. (Geburtshilfe und Frauenheilkunde, 2014)
Uterine sarcomas are rare, aggressive mesenchymal tumours with a relatively poor prognosis. The term comprises various histological subtypes, such as leiomyosarcoma, endometrial stromal sarcomas as well as undifferentiated uterine sarcomas, which require different operative and systemic/radiation therapy strategies accordingly. The evidence on operative, adjuvant and palliative treatment currently available is presented here.
Keywords: uterine carcinoma; uterus; leiomyosarcoma